Kunci Sukses Mahasiswa Universitas Negeri Jakarta: Mengungkap Peran Fasilitas Belajar dan Motivasi dalam Meningkatkan Prestasi Akademik - Tarida Alfiah Caniago (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Learning facilities refer to the physical and technological resources that students use to support learning, while learning motivation refers to the internal drive and passion that students have to learn. The purpose of this study is to determine how the influence of learning ability on the development of motivation and learning achievement of Jakarta State University students. In this study, we conducted ex post facto research and used quantitative research methods. In data collection, a sample of 110 active students of Universitas Negeri Jakarta can be obtained using the Likert scale (1-5). Data analysis techniques are generated by calculating multiple linear regression models and External Models with Convergent Reliability, Discriminant Validity, Composite Reliability, Alpha and Inner Cronbach models with statistical calculations of T, R-Square, f-Square, and VIF. The data obtained and combined from respondents' research will then be transformed with the help of SmartPLS statistical application version 4.0.9.2. From the results of the study, it can be concluded that learning facilities (Xl) and learning motivation (X2) have a significant effect on learning outcomes (Y) in Jakarta State University students.